Metaphorisation as the basis of the artistic style of oratoric prose by Georgy Konissky and Tikhon Zadonsky - Somov, Sergey E. (Journal of the Belarusian State University. Philology, 2025)
The author of the article analyses the artistic nature of the oratorical prose of two outstanding preachers of the 18th century: the Belarusian Archbishop Georgy of Mogilev (Konissky) and the Russian Bishop Tikhon Zadonsky (Sokolov). The main emphasis is on identifying and describing those leading artistic techniques that educators use when creating «words» which are church sermons that reveal the spiritual and religious content of biblical texts read during the Divine Liturgy. Among the text-forming tropes, antitheses stand out, including complex ones, presented in the form of lengthy rhetorical tirades of a prayerful nature, metonymies, comparisons, allegories, repetitions and epithets, including expressive ones, going back to the artistic nature of the biblical narrative. Metaphor (more broadly, metaphorisation), which also goes back to biblical artistry, is recognised as the main artistic device that shapes the style of the authors’ oratorical prose.
Keywords: Georgy Konissky; Tikhon Zadonsky; oratorical prose; word; biblical metaphor; metaphorisation; artistic style